Implementasi Pelayanan Online bagi Lansia Berdasarkan Spiritualitas Pentakosta - Serepina Hasibuan; Alfred Tupu (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2023)
Online-based services are still mostly carried out in Pentecostal churches even though imposition of restrictions on community activities has been officially revoked by the government at the end of 2022. This online service is a challenge in itself for elderly services, most of whom are still technologically illiterate and have many sensory limitations. On the other hand, the elderly are also part of the 'church body' whose spirituality must be maintained as well as the quality of Pentecostal spirituality. Therefore, the question posed in this article is how to implement online services for the elderly based on Pentecostal spirituality. This article aims to answer basic questions about how to implement online services for the elderly within the framework of Pentecostal spirituality. Ideally the service for the elderly can be optimized by the church both internally and externally as in the spirit of Pentecostalism even though it is done online. By using a descriptive qualitative method, the author attempts to formulate procedures for implementing online-based elderly services within the framework of Pentecostal spirituality. The results of the research lead to several actions that must be implemented, namely: first, pastoral and digital assistance for the elderly. Second, the trust to involve the elderly in communion, witness, faith and prayer conviction.